2002
DOI: 10.1093/jn/132.6.1214
|View full text |Cite
|
Sign up to set email alerts
|

Rice Expressing Lactoferrin and Lysozyme Has Antibiotic-Like Properties When Fed to Chicks

Abstract: Two experiments were conducted to determine whether rice that has been genetically produced to express human lactoferrin (LF) or lysozyme (LZ) protects the intestinal tract similarly to subtherapeutic antibiotics (bacitracin + roxarsone; Antibiotics). Experiment 1 compared 10 corn-soy diets containing 20% of various proportions of LF, LZ or conventional rice (CONV). Chicks fed 5% LF + 10% LZ + 5% CONV had significantly better feed efficiency and thinner lamina propria in the duodenum than those fed 20% CONV. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 32 publications
6
97
1
2
Order By: Relevance
“…Residual levels of 0.06-327 mg/L were found in lysozyme-treated wines [22,23], while in commercial cheeses, concentrations of 30.8-386.2 mg/kg were found to be present [24]. Lysozyme has also been used as an antibacterial agent during beer production [25], to extend the shelf-life of meat [26] and shrimp [27], as an alternative to antibiotics [28,29] in veterinary medicine or as anti-inflammatory drug in the treatment of wounds and infections [4,30].…”
Section: Properties Of Lysozyme and Its Importance For Daily Lifementioning
confidence: 99%
“…Residual levels of 0.06-327 mg/L were found in lysozyme-treated wines [22,23], while in commercial cheeses, concentrations of 30.8-386.2 mg/kg were found to be present [24]. Lysozyme has also been used as an antibacterial agent during beer production [25], to extend the shelf-life of meat [26] and shrimp [27], as an alternative to antibiotics [28,29] in veterinary medicine or as anti-inflammatory drug in the treatment of wounds and infections [4,30].…”
Section: Properties Of Lysozyme and Its Importance For Daily Lifementioning
confidence: 99%
“…Hence the need of the hour is to find an alternative to antibiotics. Therefore, search for antibiotic alternatives have already been undergoing to control the enteric diseases Ayed et al, 2004) which is encouraged by the World Health Organization (Humphrey et al, 2002). The quest for the alternatives to antibiotics has been tried by many scientists like Langhout, (2000) ;Mellor, (2000) ;Wenk, (2000) and Humphrey et al, (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, search for antibiotic alternatives have already been undergoing to control the enteric diseases Ayed et al, 2004) which is encouraged by the World Health Organization (Humphrey et al, 2002). The quest for the alternatives to antibiotics has been tried by many scientists like Langhout, (2000) ;Mellor, (2000) ;Wenk, (2000) and Humphrey et al, (2002). Humphrey et al (2002) found that lactoferrin and lysozyme are having the antibacterial activity and can be used as an alternative to antibiotics in chickens as feed additive.…”
Section: Introductionmentioning
confidence: 99%
“…However, concern has been expressed about the potential development of antibiotic resistant bacteria. Consequently, the animal feed industry, exposed to increasing consumer pressure to reduce the use of AGPs in poultry diets, has to find alternative feed additives (Humphrey et al, 2002;Botsoglou et al, 2004). Herbs could be used as alternatives to AGPs in poultry nutrition due to their antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%